Encounters with God in Augustine's Confessions : books VII-IX - Vaught, Carl G., 1939- (Albany, N.Y. : State University of New York, 2004)
This reappraisal of the middle section of Augustine's Confessions covers the period of Augustine's conversion to Christianity. The author argues against the prevailing Neoplatonic interpretation of Augustine.
Intro -- Encounters with God in Augustine's Confessions -- Contents -- Preface -- Introduction -- THE FRAMEWORK OF THE ENTERPRISE -- UNITY AND SEPARATION IN AUGUSTINE'S THINKING -- SPEAKING AND HEARING AS PRIMORDIAL PHENOMENA -- PROBLEMS OF ACCESS TO THE TEXT -- 1. The Philosophical Conversion (Book VII) -- THE CONCEPT OF GOD (7.1.1-7.2.3) -- THE PROBLEM OF EVIL (7.3.4-7.8.12) -- NEOPLATONISM AND CHRISTIANITY (7.9.13-7.9.15) -- THE NEOPLATONIC VISION (7.10.16-7.17.23) -- THE NEED FOR A MEDIATOR (7.18.24-7.21.27) -- 2. Augustine's Christian Conversion (Book VIII) -- INITIAL HESITATION (8.1.1-8.1.2) -- THE CONVERSION OF VICTORINUS (8.2.3-8.4.9) -- THE BONDAGE OF THE WILL (8.5.10-8.5.12) -- STAGES OF LIBERATION (8.6.13-8.11.27) -- THE DECISIVE MOMENT (8.12.28-8.12.29) -- THE CHRISTIAN COMMUNITY (8.12.30) -- 3. Mother and Son A Shared Mystical Experience (Book IX) -- RETIREMENT AND BAPTISM (9.1.1-9.7.16) -- MONICA'S CHARACTER (9.8.17-9.9.22) -- THE GARDEN IN OSTIA (9.10.23-9.10.26) -- THE DEATH OF AUGUSTINE'S MOTHER (9.11.27-9.13.37) -- Notes -- PREFACE -- INTRODUCTION -- CHAPTER 1 -- CHAPTER 2 -- CHAPTER 3 -- Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- R -- S -- T -- U -- V -- W.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Augustine, -- of Hippo, Saint, -- 354-430.; Augustine, -- of Hippo, Saint, -- 354-430.; Augustine, -- of Hippo, Saint, -- 354-430; Confessiones (Augustine, of Hippo, Saint); Spirituality -- Christianity -- History -- Early church, ca. 30-600.; Christian saints -- Algeria -- Hippo (Extinct city) -- Biography -- History and criticism; Christian saints -- Algeria -- Hippo (Extinct city) -- Biography -- History and criticism; Saints chrétiens -- Algérie -- Hippone (Ville ancienne) -- Biographies -- Histoire et critique; RELIGION -- Christian Church -- History; RELIGION -- Christianity -- History; Christian saints; Spirituality -- Christianity -- Early church; Algeria -- Hippo (Extinct city); 30-600; Biographies; Criticism, interpretation, etc; History